DUCTAL CARCINOMA IN SITU: CURRENT DIAGNOSTIC AND THERAPEUTIC APPROACHES - Petrović, Jelena; Stevanović, Stefan (Srpski medicinski časopis Lekarske komore, 2025)
Advancements in breast cancer screening have significantly increased the incidence of ductal carcinoma in situ (DCIS) diagnoses. Despite its favorable prognosis, DCIS poses a clinical challenge due to its biological heterogeneity and potential progression to invasive ductal carcinoma (IDC). Mammography remains the primary diagnostic modality, with microcalcifications as the most common radiological finding. Management is primarily surgical, involving either breast-conserving surgery (BCS) or mastectomy, depending on the extent of the lesion. In patients undergoing BCS, adjuvant radiotherapy is recommended to reduce the risk of local recurrence, while hormonal therapy (tamoxifen or aromatase inhibitors) is indicated for hormone receptor-positive tumors. Axillary lymph node dissection is not routinely performed but may be considered in cases with suspected microinvasion. Recently, active surveillance has emerged as a potential alternative for selected low-risk patients. Ongoing research is focused on the identification of prognostic factors to enable more precise risk stratification. This review provides an overview of current multidisciplinary approaches to the diagnosis and treatment of DCIS, based on the latest scientific evidence.